Numbers of Whooper Swans Cygnus cygnus in Iceland, Ireland and Britain in January 1995: results of the international Whooper Swan census - Cranswick, P A; Bowler, J M; Delany, S N; Einarsson, O; Gardarsson, A; McElwaine, J G; Merne, O J; Rees, E C; Wells, J H (Wildfowl, 1996)
The third co-ordinated international census of Whooper Swans in Iceland, Ireland and Britain was made in January 1995. Excellent coverage was achieved and 15,842 birds were counted or estimated, suggesting a decrease in the population of 2,193 birds (12.2% overall, or 3.0% per annum) since the previous census in January 1991; 20.1% overall if only adult birds are considered. Average annual mortality was estimated at 19.7%, compared with recruitment of 16.7%, over the four year period. Distribution was similar to 1991, however, with 5,016 (31.7%) recorded in Great Britain and the Isle of Man, 2,783 (17.6%) in Northern Ireland, 7,072 (44.6%) in the Republic of Ireland and 971 (6.1%) in Iceland. Around 400 birds wintered on the continent, whilst an unknown but probably small number from the Scandinavian/Russian population wintered in Britain. It is recommended that the figure of 16,000 is adopted for the Icelandic Whooper Swan population. The 10,156 birds aged included 1,814 (17.9%) juveniles, indicating that 1994 was a good breeding year. Substantial variation in the distribution of juveniles in the wintering range emphasises the difficulty of obtaining accurate estimates of annual productivity from small or localised samples.